2000
DOI: 10.1001/archsurg.135.11.1298
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial Iodine 131–Labeled Lipiodol as Adjuvant Therapy After Curative Liver Resection for Hepatocellular Carcinoma

Abstract: Intra-arterial lipiodol labeled with iodine 131 (131 I-lipiodol) can be safely used as adjuvant therapy following curative liver resection for hepatocellular carcinoma (HCC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 12 publications
0
29
0
2
Order By: Relevance
“…The overall recurrence was 30.1%, 62.3% and 79.0% in 1, 3, 5 years after resection of HCC, respectively [5] . Adjuvant therapies were used to prolong the survival and decrease the recurrence of HCC in different centers, such as transcatheter arterial chemoembolization (TACE) [6][7][8][9][10][11][12][13] , polyprenoic acid [14] , adoptive immunotherapy [15] , interferon [16] , and iodine-131-labeled lipiodol [17][18][19] . TACE was one of the most commonly used adjuvant managements for preventing recurrence and prolonging the survival of patients postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…The overall recurrence was 30.1%, 62.3% and 79.0% in 1, 3, 5 years after resection of HCC, respectively [5] . Adjuvant therapies were used to prolong the survival and decrease the recurrence of HCC in different centers, such as transcatheter arterial chemoembolization (TACE) [6][7][8][9][10][11][12][13] , polyprenoic acid [14] , adoptive immunotherapy [15] , interferon [16] , and iodine-131-labeled lipiodol [17][18][19] . TACE was one of the most commonly used adjuvant managements for preventing recurrence and prolonging the survival of patients postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…11 After this initial result several follow-up trials gave inconclusive results. [12][13][14] Nevertheless, the size of these trials was relatively small, and their clinical usefulness still needs confirmation in large multi-centre trials.…”
Section: Discussionmentioning
confidence: 99%
“…30 These findings indicate that I-131-Lip has potential advantages for use in hepatoma therapy. [31][32][33] The selective delivery and retention of lipiodol are thought to result from the developed neovasculature, enhanced permeability and the poor reticuloendothelial systems observed in hepatoma tissues. Despite this capacity for the selective accumulation at the tumor site, clinical studies have shown the effectiveness of such I-131-Lip therapy alone to only be temporary, and early HCC recurrence was observed in many cases.…”
Section: Discussionmentioning
confidence: 99%